2021
DOI: 10.3390/cells10071697
|View full text |Cite
|
Sign up to set email alerts
|

Tuning IgE: IgE-Associating Molecules and Their Effects on IgE-Dependent Mast Cell Reactions

Abstract: The recent emergence of anti-immunoglobulin E (IgE) drugs and their candidates for humans has endorsed the significance of IgE-dependent pathways in allergic disorders. IgE is distributed locally in the tissues or systemically to confer a sensory mechanism in a domain of adaptive immunity to the otherwise innate type of effector cells, namely, mast cells and basophils. Bound on the high-affinity IgE receptor FcεRI, IgE enables fast memory responses against revisiting threats of venoms, parasites, and bacteria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 144 publications
(231 reference statements)
0
20
0
Order By: Relevance
“…Mast cell activation can occur following many triggers and via a plethora of cell surface receptors, including receptors for IgE, IgG, complement, cytokines, growth factors, stem cell factor, and neuropeptides (beyond the scope of this review) [ 4 , 11 , 33 ]. The prototypic IgE-mediated activation ( Figure 1 ) occurs when allergen specific IgE is bound by a multivalent allergen and interacts with the high affinity receptor for immunoglobulin E (FcεR1) carried on their surfaces [ 44 , 45 ]. The high affinity receptor for IgE has a heterotetrametric structure, comprising an α-chain (binds IgE), a β-chain (plays a key role in signal transduction), and two γ-chains (that initiate signaling post-activation) [ 45 ].…”
Section: Brief Overview Of Mast Cell Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Mast cell activation can occur following many triggers and via a plethora of cell surface receptors, including receptors for IgE, IgG, complement, cytokines, growth factors, stem cell factor, and neuropeptides (beyond the scope of this review) [ 4 , 11 , 33 ]. The prototypic IgE-mediated activation ( Figure 1 ) occurs when allergen specific IgE is bound by a multivalent allergen and interacts with the high affinity receptor for immunoglobulin E (FcεR1) carried on their surfaces [ 44 , 45 ]. The high affinity receptor for IgE has a heterotetrametric structure, comprising an α-chain (binds IgE), a β-chain (plays a key role in signal transduction), and two γ-chains (that initiate signaling post-activation) [ 45 ].…”
Section: Brief Overview Of Mast Cell Biologymentioning
confidence: 99%
“…The prototypic IgE-mediated activation ( Figure 1 ) occurs when allergen specific IgE is bound by a multivalent allergen and interacts with the high affinity receptor for immunoglobulin E (FcεR1) carried on their surfaces [ 44 , 45 ]. The high affinity receptor for IgE has a heterotetrametric structure, comprising an α-chain (binds IgE), a β-chain (plays a key role in signal transduction), and two γ-chains (that initiate signaling post-activation) [ 45 ]. This process activates a downstream signaling cascade (summarized in Figure 1 ) involving immunoreceptor tyrosine-based activation motifs (ITAMS) associated with the β- and γ-chains.…”
Section: Brief Overview Of Mast Cell Biologymentioning
confidence: 99%
See 1 more Smart Citation
“… 53 , 55 , 56 Anti-IgE therapy may be effective in this regard, considering the effect on mast cells and basophils production and activation. 57 , 58 Actually, eosinophils may also have a direct role in COVID-19-related inflammation. 59 Indeed, during the first phases of respiratory infections, an active migration of circulating eosinophils from the peripheral blood to target tissues can occur, and eosinophils are known to perform some antiviral functions.…”
Section: Impact Of Anti-th2 Therapy On Covid-19: Potential Mechanismsmentioning
confidence: 99%
“…According to the reports describing cross-talk and mutual regulation between β-AR and TGF-β signaling, 16 we wonder that whether β-AR contributes to TGF-β activation and regulates cardiac hypertrophy via activation of the cAMP-PKA pathway in cardiomyocytes? Additionally, previous studies have suggested that FcεR2, the low affinity IgE receptor, may contribute to the production of chemokines, 17 that have also been shown to function directly in cardiac remodeling. 18 Therefore, we speculate that elevated IgE induces the expression of FcεR2 in cardiomyocytes and then activates the chemokine-related pathway.…”
mentioning
confidence: 99%